2004
DOI: 10.1097/00001756-200409150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MPSS and a potent iNOS inhibitor on traumatic spinal cord injury

Abstract: ONO-1714, a selective inhibitor of inducible nitric oxide synthetase (iNOS) attenuated the increase of apoptosis and improved the functional outcome of urinary bladder after traumatic spinal cord injury. These findings suggest that iNOS plays a role in the process of SCI. Early treatment with 30 mg/kg methylprednisolone sodium succinate (MPSS) could also inhibit the expression of iNOS gene, apoptosis and the loss of urinary bladder function. We confirmed that early MPSS treatment may prevent injury associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
4
17
0
Order By: Relevance
“…The results demonstrated that iNOS expression was upregulated after SCI and positively correlated to the apoptotic index. Nitric oxide (NO) is produced when nitric oxide synthase (NOS) catalyzes L-arginine to generate citrulline, and studies 22,23 have shown that overdose of NO produced by iNOS was found to induce cell apoptosis in the traumatic SCI models, so inhibition of iNOS may be an efficient therapy for secondary SCI. Our experimental results showed the percentage of iNOS-positive cells and apoptotic index of nerve cells in the EGb group was significantly lower than that in the NS group, which suggested that EGb 761 suppressed iNOS expression and then prevented nerve cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that iNOS expression was upregulated after SCI and positively correlated to the apoptotic index. Nitric oxide (NO) is produced when nitric oxide synthase (NOS) catalyzes L-arginine to generate citrulline, and studies 22,23 have shown that overdose of NO produced by iNOS was found to induce cell apoptosis in the traumatic SCI models, so inhibition of iNOS may be an efficient therapy for secondary SCI. Our experimental results showed the percentage of iNOS-positive cells and apoptotic index of nerve cells in the EGb group was significantly lower than that in the NS group, which suggested that EGb 761 suppressed iNOS expression and then prevented nerve cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Two results of the present study are difficult to reconcile, namely, that the MP group had the lowest oligodendrocyte AI and a relatively high TPC count and the other concerns the observed anti-inflammatory effect of GP. In general, it is considered that steroid therapy can enhance neurologic recovery after SCI augmenting behavior recovery and it is in fact the most widely used therapy in clinical conditions [2,32]. Nevertheless, exact mechanism of action is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, although a few studies have been conducted on the effects of steroid on neuronal and glial apoptosis, results are controversial. Yu et al [32] reported that early treatment with MP after SCI reduces inducible nitric oxide synthetase expression, and concluded that MP acts as a neuroprotector by inhibiting neuronal apoptosis. On the other hand, Li et al [18] concluded that MP treatment after SCI does not reduce the expression of caspase-3, a key enzyme of apoptosis, after rat spinal cord transection, and Diem et al [4] reported that steroid treatment has a negative effect on neuronal apoptosis in the autoimmune disease of the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal studies have shown that high-dose methylprednisolone treatment of acute spinal cord injury results in a reduction in biochemical mediators of secondary neurological injury [1][2][3][4][5][6] and significantly improved neurological function. [7][8][9][10][11] Unfortunately, results in humans have been less sanguine.…”
Section: Introductionmentioning
confidence: 99%